Magnesium alloy containing TiCN nanoparticles for selective laser melting and application of magnesium alloy

By adding nanoTiCN particles into magnesium alloy and using laser selection melting process, the problem of low mechanical properties of magnesium alloy parts is solved, and the mechanical properties of magnesium alloy molded parts are improved and the application range of magnesium alloy molded parts is achieved.

CN119410979APending Publication Date: 2025-02-11HUAZHONG UNIV OF SCI & TECH +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411291405.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-14
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

The low mechanical properties of existing magnesium alloy parts limit their application in many fields.

Method used

By adding an appropriate amount of nanoTiCN particles into the magnesium alloy and combining with the laser selective melting (SLM) process, the alloying is promoted to obtain SLM magnesium alloy molded parts with good mechanical properties.

Benefits of technology

It significantly improves the tensile strength, yield strength and creep breaking life of magnesium alloy molded parts, and expands the application range of magnesium alloys in different fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119410979A_ABST
    Figure CN119410979A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of selective laser melting rapid prototyping, and discloses a TiCN nanoparticle-containing magnesium alloy for selective laser melting and application thereof, and the TiCN nanoparticle-containing magnesium alloy powder for selective laser melting comprises the following components by mass: 8.5-9.5% of Al element, 0.5-0.9% of Zn element, 0.2-0.4% of Mn element, 1.5-2.5% of TiCN nanoparticles, less than or equal to 0.1% of impurity, and the balance of Mg element. The TiCN nanoparticles are introduced into the magnesium alloy, the selective laser melting process is matched, the mechanical property of the correspondingly obtained SLM magnesium alloy forming part is good, the ductility of the forming part is further improved through the refined and uniform magnesium alloy grain structure and dispersively distributed nano TiCN, and the tensile strength, the yield strength and the creep fracture life of the forming part are all improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field related to laser selective melting rapid prototyping, and more specifically, relates to a magnesium alloy for laser selective melting containing TiCN nanoparticles and application thereof. Background Art

[0002] Magnesium metal and its alloys are the most common and lightest metal structural materials. The main alloying elements are aluminum, zinc, manganese, cerium, thorium, and a small amount of zirconium, cadmium, bismuth, antimony, etc. Magnesium alloys have the advantages of low density, high strength, good thermal conductivity and electrical conductivity, good resistance to organic and alkali corrosion, and are widely used in aerospace, biomedicine, automotive industry, military equipment and other fields due to their excellent properties such as high specific strength and biocompatibility. For example, in the automotive industry, the lightweight advantage of magnesium alloys is particularly prominent. With the rise of new energy vehicles, the application of magnesium alloys in battery trays, battery pack shells and other components is also increasing. In biomedicine, magnesium alloys can be used to manufacture vascular stents, tooth repair materials, etc. due to their good biocompatibility and degradability.

[0003] Laser additive manufacturing technology first builds a three-dimensional model, uses a high-energy laser beam to melt metal powder, and then stacks it layer by layer to achieve precision molding of complex parts. Compared with the high manufacturing cost and long working cycle of traditional casting processes, laser additive manufacturing technology can quickly process parts with complex structures and ensure that the parts have high dimensional accuracy. Selective laser melting (SLM) is currently a major technical approach in the field of laser additive manufacturing technology. According to the path planned in the three-dimensional CAD slice model, the high-energy laser transmitter scans the metal powder bed layer by layer to completely melt the metal powder to achieve metallurgical bonding. No binder is required, and it is directly molded during solidification. Due to the fast cooling rate, the grains are small and have excellent mechanical properties. Due to its principle and characteristics of molding preparation, laser selective melting technology has four main advantages: it is suitable for complex structures, has a wide range of molding materials, has high comprehensive mechanical properties, and is suitable for personalized customization. It is a popular research direction and future development trend of rapid prototyping additive manufacturing.

[0004] At present, the molding method of magnesium alloy parts is mainly casting, with light weight as its biggest feature, but the mechanical properties still have room for improvement. The tensile strength of cast AZ91D magnesium alloy parts is about 250Mpa, the yield strength is about 150MPa, and the elongation is about 7%. The relatively low mechanical properties limit the application of magnesium alloys in many fields. Therefore, new preparation methods such as laser selective melting (SLM) are urgently needed to replace traditional methods to obtain SLM magnesium alloy molded parts with good mechanical properties. Summary of the invention

[0005] In view of the above defects or improvement needs of the prior art, the present invention provides a magnesium alloy powder for laser selective melting modified with nano-TiCN and its application, wherein the specific composition of the magnesium alloy powder for laser selective melting is improved, an appropriate amount of nano-TiCN particles are added to the magnesium alloy, and the SLM process is used to promote its alloying to obtain SLM magnesium alloy molded parts with good mechanical properties, thereby solving the technical problem that traditional preparation methods limit the mechanical properties and application scope of magnesium alloys.

[0006] To achieve the above-mentioned purpose, according to one aspect of the present invention, a magnesium alloy powder for laser selective melting is provided, which is composed of the following components in mass percentage: 8.5-9.5% Al element, 0.5-0.9% Zn element, 0.2-0.4% Mn element, 1.5-2.5% TiCN nanoparticles, impurities ≤0.1%, and the rest is Mg element.

[0007] Preferably, the particle size of the powder is in the range of 15 to 53 μm, the particle size of the TiCN nanoparticles is in the range of 50 to 900 nm, and the TiCN nanoparticles are dispersed in the powder.

[0008] According to another aspect of the present invention, a method for preparing magnesium alloy powder for selective laser melting is provided, comprising the following steps:

[0009] S1: synthesizing TiCN nanoparticle powder by a sol-gel method, and ball-milling the synthesized TiCN nanoparticle powder so that the particle size of the TiCN nanoparticles is in the range of 50 to 900 nm; preparing raw magnesium alloy powder by using a raw magnesium alloy containing Al, Zn and Mn elements as a raw material; ball-milling the raw magnesium alloy powder to control the particle size of the raw magnesium alloy powder to be 15 to 53 μm;

[0010] S2: Drying the raw magnesium alloy powder and the TiCN nanoparticle powder separately to make the powders fully dry;

[0011] S3: The dried raw magnesium alloy powder and the TiCN nanoparticle powder are proportioned and mixed according to the target mass percentage of each component in the magnesium alloy powder for selective laser melting, and the mixing is specifically carried out by ball milling and physical powder mixing to obtain the target magnesium alloy powder for selective laser melting.

[0012] Preferably, in step S2, the drying process for each powder is specifically to dry the powder in a vacuum drying oven at 60° C. for 4 hours.

[0013] According to another aspect of the present invention, the present invention provides the use of the above magnesium alloy powder in laser selective melting, which specifically comprises the following steps:

[0014] (1) Drying the magnesium alloy powder for laser selective melting and preheating the substrate to a certain temperature;

[0015] (2) The magnesium alloy powder for selective laser melting is used to perform selective laser melting in an inert atmosphere. The scanning strategy adopted is strip scanning, and the magnesium alloy formed part is obtained by scanning layer by layer.

[0016] As a further preferred embodiment of the present invention, in the step (1), the preheating temperature used for preheating the substrate is 160-190°C.

[0017] As a further preferred embodiment of the present invention, in the step (2), the process parameters of the laser selective melting are set as follows: laser output power 150-250 W, layer thickness 30-40 μm, scanning speed 200-500 mm / s, scanning spacing 80-120 μm, scanning strategy is band scanning, and the angle is 67°.

[0018] As a further preferred embodiment of the present invention, in step (2), the inert atmosphere is an argon atmosphere;

[0019] Preferably, the oxygen content of the molding cavity corresponding to the laser selective melting is less than 200 ppm;

[0020] More preferably, the inert atmosphere is a pure argon atmosphere.

[0021] According to another aspect of the present invention, the present invention provides a magnesium alloy formed part obtained by the above application.

[0022] In general, the above technical solutions conceived by the present invention have the following beneficial effects compared with the prior art:

[0023] 1. The present invention adds an appropriate amount of TiCN nanoparticle powder to the traditional magnesium alloy powder to obtain a new magnesium alloy powder as a powder raw material for laser selective melting, and cooperates with the SLM process to promote its alloying, thereby improving the mechanical properties of the magnesium alloy molded parts, and enhancing the tensile strength, yield strength and creep rupture life of the magnesium alloy molded parts. In addition, considering that the SLM process is known to have a better SLM process effect when the particle size of the powder raw material used is 15 to 53 μm, therefore, the particle size of the new magnesium alloy powder obtained by the present invention can also be preferably 15 to 53 μm.

[0024] 2. The present invention strictly controls the addition amount of TiCN nanoparticles to strictly control the mass percentage of TiCN in the magnesium alloy system to 1.5-2.5%, effectively ensuring the mechanical strength and ductility of magnesium alloy molded parts. TiCN nanoparticles are dispersed in the magnesium alloy composite material, playing a role of dispersion strengthening; and the dispersed TiCN nanoparticles act as heterogeneous nucleation sites, greatly increasing the number and rate of nucleation, inhibiting the growth of magnesium alloy grains, inhibiting the expansion of cracks, and providing higher mechanical properties for the refined magnesium alloy grains through strengthening grain boundaries, dislocation strengthening caused by local mismatch stress, and Orowan strengthening of nano-TiCN in the grains. The refined and uniform grain structure and dispersed nano-TiCN further improve the ductility of the material.

[0025] 3. The present invention optimizes the process parameters of laser selective melting, minimizes the residual stress in the laser selective melting process, and improves the thermal process in the printing process through preheating treatment and belt scanning strategy, further reducing the thermal stress generated in the printing process. Among them, the laser selective melting adopted has a laser power of 150-250W, a scanning speed of 200-500mm / s, a layer thickness of 30-40μm, a scanning spacing of 80-120μm, and a belt scanning strategy. The target magnesium alloy molded parts are scanned layer by layer, which further ensures the improvement of mechanical strength and creep rupture life. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 is a flow chart of a method for preparing a magnesium alloy material and a high-strength magnesium alloy material based on SLM technology in an embodiment of the present invention;

[0027] Figure 2 is the stress-strain curve of the high-strength magnesium alloy sample obtained in Example 1;

[0028] Figure 3 is the stress-strain curve of the high-strength magnesium alloy sample obtained in Example 2;

[0029] Figure 4 This is the stress-strain curve of the high-strength magnesium alloy sample obtained in Example 3. DETAILED DESCRIPTION

[0030] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. In addition, the technical features involved in the various embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.

[0031] The laser selective melting magnesium alloy composite material powder of the present invention has the following components: 8.5-9.5% Al, 0.5-0.9% Zn, 0.2-0.4% Mn, 1.5-2.5% TiCN nanoparticles, ≤0.1% impurities, and the rest is Mg.

[0032] Based on the component ratio of the magnesium alloy powder for selective laser melting in the present invention, the magnesium alloy powder for selective laser melting can be prepared according to the following steps:

[0033] Step A, ball-milling the magnesium alloy material into powder, and fully mixing it with TiCN particles according to the mass percentage ratio of the target component to uniformly disperse it;

[0034] Step B, placing the mixed composite material of the two powders into a vacuum oven and performing vacuum drying at 60° C. for 4 hours;

[0035] Step C: further ball-milling and physically mixing the magnesium alloy powder composite material to control its particle size distribution to be 15-53 μm, thereby ensuring the spreading effect before printing and the fluidity during printing, and preventing the nano powder from agglomerating and affecting the molding effect.

[0036] Similar to the SLM process in the prior art, the SLM process using the magnesium alloy powder for laser selective melting in the present invention (the powder can be filled in a molding cavity equipped with a powder distribution filler inside the SLM equipment, and the powder can be evenly spread on the substrate) can specifically include the following steps:

[0037] Step 1: Install the substrate in the molding cavity and preheat it to a temperature of 160°C-190°C; the substrate may be a plate of magnesium alloy material with a thickness greater than or equal to 2 cm;

[0038] Step 2: Pass inert gas into the molding chamber to deoxygenate the molding chamber so that the oxygen content in the chamber is controlled at 200 ppm or less;

[0039] Step 3: Perform SLM molding. The process parameters of laser selective melting are set as follows: laser power is 150-250 W, scanning speed is 200-500 mm / s, layer thickness is 30-40 μm, and scanning spacing is 80-120 μm.

[0040] Step 4: Print according to the set parameters, adopt a strip scanning strategy, and scan layer by layer to obtain high-strength magnesium alloy parts.

[0041] The following experiments were conducted using commercially available aerosolized AZ91D powder as raw material.

[0042] Example 1

[0043] A magnesium alloy powder for laser selective melting containing TiCN particles, comprising the following elements by mass fraction:

[0044] Al element: 8.9%, Zn element: 0.5%, Mn element: 0.3%, TiCN nanoparticles: 1.5%, impurities: ≤0.1%, and the rest is Mg element.

[0045] (1) ball-milling the magnesium alloy powder obtained by the gas atomization method, mixing it with nano-TiCN particles in accordance with the mass percentage, ball-milling again to control the powder particle size to 15-53 μm, and drying the ball-milled powder in an oven at 60° C. for 4 h to obtain a raw material powder for laser selective melting;

[0046] (2) Processing the magnesium alloy sheet into a 2 cm thick printing substrate and preheating it at 160°C;

[0047] (3) Deoxidize the molding cavity to control the internal oxygen content to less than 200 ppm;

[0048] (4) SLM molding was performed in a pure argon atmosphere environment. The specific process parameters were set as follows: laser power of 200 W, scanning speed of 500 mm / s, layer thickness of 30 μm, scanning spacing of 100 μm, scanning strategy of strip scanning, angle of 67°, and high-strength magnesium alloy parts were obtained by scanning layer by layer;

[0049] (5) The tensile test of the sample of this example was cooled to room temperature, and its tensile strength was measured to be 237MPa and the yield strength was 182MPa. Compared with the conventional cast AZ91D magnesium alloy (see Comparative Example 1 below), the yield strength was increased by 21.3%; the elongation at break was 6.8%; the obtained molded part was subjected to a constant tensile force of 70MPa at 150°C, and the creep rupture life was 101h, which was 4.1% higher than that of the conventional cast AZ91D magnesium alloy.

[0050] Example 2

[0051] A magnesium alloy powder for laser selective melting containing TiCN particles, comprising the following elements by mass fraction:

[0052] Al element: 8.9%, Zn element: 0.5%, Mn element: 0.3%, TiCN nanoparticles: 2.0%, impurities: ≤0.1%, and the rest is Mg element.

[0053] (1) ball-milling the magnesium alloy powder obtained by the gas atomization method, mixing it with nano-TiCN particles in accordance with the mass percentage, ball-milling again to control the powder particle size to 15-53 μm, and drying the ball-milled powder in an oven at 60° C. for 4 h to obtain a raw material powder for laser selective melting;

[0054] (2) Processing the magnesium alloy sheet into a 2 cm thick printing substrate and preheating it at 160°C;

[0055] (3) Deoxidize the molding cavity to control the internal oxygen content to less than 200 ppm;

[0056] (4) SLM molding was performed in a pure argon atmosphere environment. The specific process parameters were set as follows: laser power of 200 W, scanning speed of 500 mm / s, layer thickness of 30 μm, scanning spacing of 100 μm, scanning strategy of strip scanning, angle of 67°, and high-strength magnesium alloy parts were obtained by scanning layer by layer;

[0057] (5) The tensile test of the sample of this example was cooled to room temperature, and its tensile strength was measured to be 293MPa and the yield strength was 225MPa. Compared with the traditional cast AZ91D magnesium alloy, the tensile strength increased by 17.2%, the yield strength increased by 21.3%; the elongation at break was 7.2%; the obtained molded part was subjected to a constant tensile force of 70MPa at 150°C, and the creep rupture life was 148h, which was 52.6% higher than that of the traditional cast AZ91D magnesium alloy.

[0058] Example 3

[0059] A magnesium alloy powder for laser selective melting containing TiCN particles, comprising the following elements by mass fraction:

[0060] Al element: 8.9%, Zn element: 0.5%, Mn element: 0.3%, TiCN nanoparticles: 2.5%, impurities: ≤0.1%, and the rest is Mg element.

[0061] (1) ball-milling the magnesium alloy powder obtained by the gas atomization method, mixing it with nano-TiCN particles in accordance with the mass percentage, ball-milling again to control the powder particle size to 15-53 μm, and drying the ball-milled powder in an oven at 60° C. for 4 h to obtain a raw material powder for laser selective melting;

[0062] (2) Processing the magnesium alloy sheet into a 2 cm thick printing substrate and preheating it at 160°C;

[0063] (3) Deoxidize the molding cavity to control the internal oxygen content to less than 200 ppm;

[0064] (4) SLM molding was performed in a pure argon atmosphere environment. The specific process parameters were set as follows: laser power of 200 W, scanning speed of 500 mm / s, layer thickness of 30 μm, scanning spacing of 100 μm, scanning strategy of strip scanning, angle of 67°, and high-strength magnesium alloy parts were obtained by scanning layer by layer;

[0065] (5) The tensile test of the sample of this example was cooled to room temperature, and its tensile strength was measured to be 263MPa and the yield strength was 219MPa. Compared with the traditional cast AZ91D magnesium alloy, the tensile strength increased by 5.2%, the yield strength increased by 46%; the elongation at break was 5.7%; the obtained molded part was subjected to a constant tensile force of 70MPa at 150°C, and the creep rupture life was 129h, which was 24.8% higher than that of the traditional cast AZ91D magnesium alloy.

[0066] In addition, in addition to the above-mentioned embodiments 1-3, the present invention also conducted orthogonality experiments on different SLM process parameters, with the laser output power varying in the range of 150-250W with a step length of 10W, the scanning speed varying in the range of 200-500mm / s with a step length of 100mm / s, the layer thickness varying in the range of 30-40μm with a step length of 10μm, and the scanning spacing varying in the range of 80-120μm with a step length of 20μm. The results show that when the laser power is 150-250W, the scanning speed is 200-500mm / s, the layer thickness is 30-40μm, the scanning spacing is 80-120μm, and the scanning strategy is strip scanning, all have good SLM molding effects.

[0067] Comparative Example 1

[0068] This example is used for comparison with the above four embodiments, that is, based on the traditional cast AZ91D magnesium alloy material, composed of the following elements by mass fraction:

[0069] Al element: 9%, Zn element: 0.5%, Mn element: 0.3%, no TiCN added, impurities: ≤0.1%, the rest is Mg element.

[0070] The casting has a tensile strength of 250 MPa, a yield strength of 150 MPa, an elongation at break of 6.9%, and a creep rupture life of 97 h at 150° C. and 70 MPa.

[0071] Comparative Example 2

[0072] This example is used for comparison with the above four embodiments, that is, the AZ91D magnesium alloy material based on SLM laser selective melting technology is composed of the following elements by mass fraction:

[0073] Al element: 9%, Zn element: 0.5%, Mn element: 0.3%, no TiCN added, impurities: ≤0.1%, the rest is Mg element.

[0074] (1) ball-milling the magnesium alloy powder obtained by the gas atomization method, mixing it with nano-TiCN particles in accordance with the mass percentage, ball-milling again to control the powder particle size to 15-53 μm, and drying the ball-milled powder in an oven at 60° C. for 4 h to obtain a raw material powder for laser selective melting;

[0075] (2) Processing the magnesium alloy sheet into a 2 cm thick printing substrate and preheating it at 160°C;

[0076] (3) Deoxidize the molding cavity to control the internal oxygen content to less than 200 ppm;

[0077] (4) SLM molding was performed in a pure argon atmosphere environment. The specific process parameters were set as follows: laser power of 200 W, scanning speed of 500 mm / s, layer thickness of 30 μm, scanning spacing of 100 μm, scanning strategy of strip scanning, angle of 67°, and high-strength magnesium alloy parts were obtained by scanning layer by layer;

[0078] (5) The comparative sample was cooled to room temperature after tensile test, and its tensile strength was measured to be 218 MPa, yield strength was 166 MPa, elongation at break was 6.4%, and creep rupture life at 150°C and 70 MPa was 82 h.

[0079] As shown in Table 1, the mechanical properties of the printed magnesium alloy samples with nano-TiCN particles added are better than those of the printed samples of Comparative Example 2 without nano-TiCN particles, and the mechanical properties of Examples 2 and 3 are better than those of traditional cast magnesium alloys when appropriate amounts of nano-TiCN particles are added. With the increase in the content of nano-TiCN, the mechanical properties of the samples show a trend of first increasing and then decreasing. It may be that the excessively introduced TiCN aggregates at the grain boundaries and becomes the starting point for crack diffusion, reducing its positive effect on the mechanical properties of the printed samples. In summary, adding an appropriate amount of TiCN nanoparticle powder to traditional magnesium alloy powder to obtain a new type of magnesium alloy powder as a powder raw material for laser selective melting can improve the mechanical properties of magnesium alloy molded parts by promoting its alloying in conjunction with the SLM process.

[0080] Table 1 Comparison of sample data results

[0081]

[0082] It will be easily understood by those skilled in the art that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A magnesium alloy powder for selective laser melting, characterized in that: The invention is composed of the following components in mass percentage: 8.5-9.5% Al element, 0.5-0.9% Zn element, 0.2-0.4% Mn element, 1.5-2.5% TiCN nanoparticles, impurities less than or equal to 0.1%, and the rest being Mg element.

2. The magnesium alloy powder for selective laser melting according to claim 1, characterized in that: The particle size of the powder is in the range of 15 to 53 μm, the particle size of the TiCN nanoparticles is in the range of 50 to 900 nm, and the TiCN nanoparticles are dispersed in the powder.

3. The method for preparing magnesium alloy powder for selective laser melting according to claim 1 or 2, characterized in that: The following steps are involved: S1: synthesizing TiCN nanoparticle powder by a sol-gel method, and ball-milling the synthesized TiCN nanoparticle powder so that the particle size of the TiCN nanoparticles is in the range of 50 to 900 nm; using a magnesium alloy containing Al, Zn and Mn elements as a raw material to prepare a raw magnesium alloy powder; ball-milling the raw magnesium alloy powder to control the particle size of the raw magnesium alloy powder to be 15 to 53 μm; S2: Drying the raw magnesium alloy powder and the TiCN nanoparticle powder separately to make the powders fully dry; S3: Proportioning and mixing the dried raw magnesium alloy powder and the TiCN nanoparticle powder according to the target mass percentage of each component in the magnesium alloy powder for selective laser melting, wherein the mixing is specifically performed by ball milling and physical powder mixing, so as to obtain the target magnesium alloy powder for selective laser melting.

4. The preparation method according to claim 3, characterized in that: In step S2, each powder is dried in a vacuum drying oven at 60° C. for 4 hours.

5. Use of the magnesium alloy powder as claimed in claim 1 or 2 in laser selective melting.

6. The use according to claim 5, characterized in that: The specific steps include: (1) Drying the magnesium alloy powder for laser selective melting and preheating the substrate to a certain temperature; (2) The magnesium alloy powder for selective laser melting is used to perform selective laser melting in an inert atmosphere, and a magnesium alloy molded part is obtained by scanning layer by layer.

7. The use according to claim 6, characterized in that: In the step (1), the substrate is preheated at a temperature of 160 to 190°C.

8. The use according to claim 6, characterized in that: In the step (2), the process parameters of the laser selective melting are set as follows: laser output power 150-250 W, layer thickness 30-40 μm, scanning speed 200-500 mm / s, scanning spacing 80-120 μm, scanning strategy is strip scanning, and the angle is 67°.

9. The use according to claim 6, characterized in that: In the step (2), the inert atmosphere is an argon atmosphere; Preferably, the oxygen content of the molding cavity corresponding to the laser selective melting is less than 200 ppm; More preferably, the inert atmosphere is a pure argon atmosphere.

10. A magnesium alloy formed part obtained by the application as claimed in any one of claims 6 to 9.

Citation Information

Cited By

  • Corrosion-resistant magnesium alloy adapting to selective laser melting

    CN122382428A